COMPARISON OF THE DRYER AIR INLET POSITION ON THE SPRAY DRYER WITH A DOUBLE CONDENSER TO PRODUCE A ROTATING FLOW THROUGHOUT THE DRYING CHAMBER: CFD ANALYSIS - Ruhyat, Nanang (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2023)
Simulation of the drying air and the spray of liquid in the spray dryer chamber with Discrete Phase Material (DPM) and Discrete Random Walk (DRW) was presented in this study using CFD methods to analyze the drying liquid. The main problem in spray drying is the adhesion of the material to the drying chamber walls, which causes uneven drying material. This adhesion can slow down the drying process and reduce productivity. The design of the drying air inlet into the drying chamber becomes essential to research. Variations in the position of the drying air inlet into the drying chamber are carried out in the 3D spray dryer room to see the mechanism of the centrifugal velocity of the drying airflow, which can improve uniform mixing with flow resistance due to friction with small walls and the drying air velocity. This phenomenon is impossible to observe in experiments. A geometric model consisting of 1,054,000 hexa-mesh elements at the area around the nozzle, the top spot of the chamber and the remaining area covered with a tetrahedral mesh, was determined to predict velocity, temperature, and fluid flow behavior. The first position, the dryer air inlet, is at an angle from the diameter of the spray drying chamber. The second position is in the middle of the diameter of the drying chamber. The position of the first inlet produces a more even temperature contour with a more tangential velocity due to the small frictional resistance with the walls. At the same time, the second position is not recommended because the flow leads to one side of the wall and creates sticking and even material buildup. A double-heated condenser can dry air at moderate temperatures, and it is a very effective drying product— positioning the dryer air inlet into the drying chamber, achieving the economical production of high-quality products.